Risk-Based Evaluation of Large-Span Roof Building Structure using Roll Forming Construction Method to Increase Project Performance - Batara Arifin Sirait; Yusuf Latief (Journal of International Conference Proceedings, 2022)
The large-span roof that is applied to many buildings nowadays are having some unique structural components, seen from its construction concept and design concept. Because of its uniqueness, several obstacles need to be considered. The application of roll forming machine in the making of the roof sheets can be used as a solution for several disputes that can happen while installing the large-span roof. The purpose of this research is to identify risk factors in large-span roof construction projects using the roll forming method. This research recruited 43 respondents in 24 different contractor companies. Based on the result of the questionnaire validation, this research analyzed 40 sub-variables need to be proceed into the qualitative risk analysis. Based on the outcome of the risk index assessment, there are 2 levels that need further scrutiny. It is the very high level of risk and the high level of risk. Regarding the risk level, some suggested strategy to improve the construction is to appoint an appropriate consultant, contractor, and construction management consultant, planning the detailed design and construction method, coordinate the roofing steel structure division, conduct some training for workers, and build a good collaboration between all stakeholders.Keywords: Construction Method, Large-span Roof, Project Management, Roll Forming, Risk Management, Roof Structure